2021
DOI: 10.4103/psychiatry.indianjpsychiatry_930_20
|View full text |Cite
|
Sign up to set email alerts
|

Study of screening of mental health status of coronavirus disease-19 confirmed noncritical patients admitted at a tertiary care hospital and a coronavirus disease care center in Ahmedabad

Abstract: Background: Despite coronavirus disease-19 (COVID-19) being a major health crisis in the current times, only a few studies have addressed its potential direct effect on mental health, especially among COVID-19 patients. Aims: This study was conducted to assess the mental health of COVID-19 patients. Materials and Methods: In cross sectional study, mental health status of 301 symptomatic and 200 asymptomatic COVID-19 participants was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(17 reference statements)
0
2
1
Order By: Relevance
“…22 Patients with physical and psychiatric comorbidities were found to be more anxious in other studies but we did not find significant difference of perceived stress and coronavirus-specific anxiety level compared with those without these ailments. 23,25 Prolonged hospital stay was associated with the higher level of distress and mean duration of hospital stay in our study was 10.2 (±4.4) days, shorter compared to similar studies. 22,26 The course of illness during hospital stay would be the more relevant predictor, as patients treated in high dependency units were more anxious and distressed than those who stayed in general ward throughout their course in the hospital.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…22 Patients with physical and psychiatric comorbidities were found to be more anxious in other studies but we did not find significant difference of perceived stress and coronavirus-specific anxiety level compared with those without these ailments. 23,25 Prolonged hospital stay was associated with the higher level of distress and mean duration of hospital stay in our study was 10.2 (±4.4) days, shorter compared to similar studies. 22,26 The course of illness during hospital stay would be the more relevant predictor, as patients treated in high dependency units were more anxious and distressed than those who stayed in general ward throughout their course in the hospital.…”
Section: Discussioncontrasting
confidence: 54%
“…Age distribution was fairly in concordance with other similar studies in India. [22][23][24][25][26][27][28] Most studies observed either equal gender distribution or female predominance like us except Kumar et al 24 Although Somani et al, did not find any association between distress with respect to age, gender, marital status, education, or occupation among general population; the scenario was different among COVID-19 patients. 29 The level of perceived stress was more in females but no gender difference noted for coronavirus-specific anxiety in our study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Critically ill patients account for the largest number of psychiatric consultations [6]. Parikh et al evaluated the mental health of COVID-19 patients in India and results showed that symptomatic patients were relatively more psychological distressed than asymptomatic patients [7]. Alamri et al investigated the mental health of COVID-19 patients in Saudi Arabia and observed that 50% of COVID-19 patients were considered to have anxiety and depression or demonstrated a borderline level of anxiety and depression [8].…”
Section: Introductionmentioning
confidence: 99%